1993
DOI: 10.1520/jfs13449j
|View full text |Cite
|
Sign up to set email alerts
|

Aspartic Acid Racemization in Intervertebral Discs as an Aid to Postmortem Estimation of Age at Death

Abstract: We investigated whether measurement of aspartic acid racemization in intervertebral discs (IVD) could be used in the postmortem estimation of age at death. The extent of aspartic acid racemization in IVD tissues was found to increase with age. The rate of racemization turned out to be much higher in the nucleus pulposus than in the annulus fibrosus. The relation between age and the D-aspartic acid content in the anterior peripheral annulus fibrosus of IVD was close enough to allow postmortem estimation of age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
2

Year Published

1993
1993
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 22 publications
2
24
0
2
Order By: Relevance
“…tion has also been studied in the acid-soluble and -insoluble collagen-rich fraction of human rib cartilage (19) and in the nucleus pulposus and annulus fibrosis from the intervertebral disc (21). In these studies, estimated aspartic acid racemization rates in cartilagenous tissues were 4 -10-fold higher (0.108 -0.236% D-Asp per year (19,21)) than our estimation for cartilage collagen (0.0258% D-Asp per year). Unfortunately, the protocols used in these studies result in significant amounts of residual proteoglycans in the collagen preparations.…”
Section: Racemization Of Aspartic Acid In Human Cartilage Collagen Anmentioning
confidence: 67%
See 1 more Smart Citation
“…tion has also been studied in the acid-soluble and -insoluble collagen-rich fraction of human rib cartilage (19) and in the nucleus pulposus and annulus fibrosis from the intervertebral disc (21). In these studies, estimated aspartic acid racemization rates in cartilagenous tissues were 4 -10-fold higher (0.108 -0.236% D-Asp per year (19,21)) than our estimation for cartilage collagen (0.0258% D-Asp per year). Unfortunately, the protocols used in these studies result in significant amounts of residual proteoglycans in the collagen preparations.…”
Section: Racemization Of Aspartic Acid In Human Cartilage Collagen Anmentioning
confidence: 67%
“…There is a close relationship between chronological age and D-aspartic acid accumulation in the white matter of the brain (17), the eye lens (16), dentin (18), and bone (19,20). Furthermore, several studies have shown the age-related accumulation of D-aspartic acid in cartilagenous tissues such as the intervertebral disc (21), rib cartilage (22), and articular cartilage (11,23). Measurement of aspartic acid racemization has proven to be a valuable tool to derive quantitative information on protein residence time, i.e.…”
mentioning
confidence: 99%
“…Several sites in the human body, including lung (Shapiro et al 1991), heart (Powell et al 1992), brain (Shapira et al 1988), teeth (Helfman and Bada 1975), skin (Verzijl et al 2000), intervertebral discs (Ritz and Schutz 1993) and cartilage (Maroudas et al 1992) contain abundant proteins that are very long-lived, with half-lives measured in decades.…”
Section: Introductionmentioning
confidence: 99%
“…[49][50][51] Agedependent amino acid racemization also has been observed in proteins found in vertebral discs and the eye lens. [52][53][54][55] In theory, the racemization process is not directly coupled to the aging of the individual, but is simply a process that depends on when proteins were first generated in the body.…”
Section: Chemical and Molecular Biological Methodsmentioning
confidence: 99%